REMOTE ESTIMATION OF TOTAL SUSPENDED SOLID (TSS) TRANSPORT AFFECTED BY TIDAL BORE “BONO” OF KAMPAR BIG RIVER ESTUARY USING LANDSAT 8 OLI IMAGERY - Wisha, Ulung Jantama; Dhiauddin, Ruzana; Kusumah, Gunardi (Research Center for Oceanography - Indonesian Institute of Sciences (LIPI), 2017)
The Kampar River estuary has a unique tidal bore, namely Bono. A tidal bore is a natural phenomenon caused by the tidal flow which meet the flow of the river. Tidal bore